An analysis on the impact of human capital development on economic growth in the Philippines - Rona O. Navarro, Irene Mae O. Porras, Matthew Freddy A. Racadio, Glen Mark C. Ramos 4 0 16; 5
u
Research Paper: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2021
Keywords: 2 -- 0; 6; 20; 20; 2